2017
DOI: 10.1111/cid.12469
|View full text |Cite
|
Sign up to set email alerts
|

A novel conversion method for radiographic guide into surgical guide

Abstract: The novel method for converting a radiographic guide into a surgical guide appears accurate and stable compared with SLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…3). To calculate the marginal gaps, the original standard and silicone-coated models were digitally mapped by accuracy analysis module of MIRDC Dental software (Metal Industry Research Development Centre, Kaohsiung, Taiwan) 3 . The superimposition of these two models was performed by aligning the corresponding matrix based on a number of planes (mesial, distal, buccal, and lingual) and mapped points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). To calculate the marginal gaps, the original standard and silicone-coated models were digitally mapped by accuracy analysis module of MIRDC Dental software (Metal Industry Research Development Centre, Kaohsiung, Taiwan) 3 . The superimposition of these two models was performed by aligning the corresponding matrix based on a number of planes (mesial, distal, buccal, and lingual) and mapped points.…”
Section: Methodsmentioning
confidence: 99%
“…High-quality restorations can be achieved by experienced dental technicians in a series of precision conventional lost wax and casting manufacturing processes. Recently, more and more digital technologies, such as the dental computer-aided design and computer-aided manufacturing (CAD/CAM) system (subtractive manufacturing) 1 , 2 or the surgical planning system, 3 , 4 have been developed to assist clinicians to complete treatments effectively. In these digital systems, the dental CAD/CAM systems are generally used to improve the effectiveness of prosthesis fabrications.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of stability is a danger, since it can determine spatial deviations in the insertion of the implants, compared to the original planning [2, 3, 6, 18, 21, 22]. Such deviations do not necessarily lead to invasion of dangerous anatomical structures, but may result in an implant placement that is too buccal, which may lead to complications and aesthetic sequelae [3, 6, 18, 21, 22, 26], or insertion too close to other teeth or implants. All these situations can complicate the prosthetic rehabilitation, forcing the dental technician to adopt compromise solutions.…”
Section: Introductionmentioning
confidence: 99%
“…For laboratory milled surgical guide, the most critical step is to transfer the virtual implant position into the coordinates of the milling machine. Previous studies have reported several transfer methods, such as the "X-cube", orthogonally designed acrylic rods or a standard template [9,10]. In 2018, a kind of implant surgical guide fabricated using 5-axis Computer Numerical Control (CNC) milling machine for guided implant placement in the edentulous jaw was introduced [11].…”
Section: Introductionmentioning
confidence: 99%